Learner Autonomy and Some Selected Correlates among Adult Distance Learners in Malaysia - Ng, Siew Foen (2009)
Studies have indicated that the lack of self-regulated learning skills, or the inability to function autonomously may lead to adults dropping out of courses, failing to enroll in subsequent courses, and overall dissatisfaction with learning in distance courses (Calvin, 2005; Hisham, 2004; Zimmerman, 2001). Confessore, (1992) asserts that success is ultimately dependent upon the individual’s personal characteristics that define learner autonomy which lie in the psychological paradigm of individuals. This study examined to what extent distance learners in Malaysia are autonomous by investigating learner autonomy level among distance learners undertaking learning in the distance learning environments. Adult learners come from different background, skills and experiences and thus, may contribute to the different approaches and attitude towards learning. The adult learners’ diversified background in terms of their learning styles, perception towards learning environment, computer technology experiences and English language proficiency may influence their learner autonomy or intentions to participate actively and productively in a learning process. Thus, this study also examined whether these variables predicted the adult learners’ learner autonomy. A stratified structured sampling was used to select 370 adult distance learners of three universities in Malaysia which offered distance learning program. Data was gathered using self-administered questionnaires. Two hundred and forty nine distance learners or 69% of them completed and returned the survey questionnaires in this study. The results of the descriptive analyses revealed that distance learners in Malaysia showed a relatively low level of learner autonomy in their intention to participate in learning. Using Pearson’s correlation analysis, the study found significant correlations of learning styles, perceived learning environment, computer technology experience and English language proficiency to the learner autonomy profile (LAP) scores. Chi-square test of independence revealed that the higher the learner autonomy scores, the more learning styles were being utilized in learning. The distance learners perceived that environmental supports such as personal relevance in the course structure, instructor support and satisfaction enhanced learner autonomy. In similar vein, distance learners also indicated the importance of computer technology experiences and English language proficiency. Both variables showed moderate correlation with distance learners' intentions to participate actively in their learning. The Multiple Regression analysis revealed that the number of learning styles, perceived learning environment and computer technology experience showed statistically predictive of learner autonomy or distance learners’ intention to participate. However, English language proficiency was not included as a significant predictor of learner autonomy. The overall regression model was successful in explaining approximately 39.7% of the adjusted variance in learner autonomy. The model proposed is considered a good model as the results demonstrated that the overall scores of the three predictors show statistically significant in contributing to the variance of the criterion variable. All the hypotheses in the study were supported. The results of this study provided a number of theoretical and practical implications on the learner autonomy among distance learners in Malaysia. Recommendations were suggested to facilitate higher learner autonomy among distance learners. The need for further research on the learner autonomy was also highlighted.